Application and validation of ukrainian-language modification of the ferrans and powers quality of life questionnaire for patients with heart rhythm distirancies in Ukraine - Brynza, Mariia (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2021)
Introduction. Atrial flutter (AFl) and atrial fibrillation (AF) are ones of the most common arrhythmias, they constitute a significant proportion of cardiovascular events. Radiofrequency ablation (RFA) is the most common strategy of rhythm control in these patients, affects many endpoints, including quality of life. Existing validated questionnaires are not specific, need a lot of time as for patient during filling in, as for doctor during interpretation. In English resources Ferrans and Powers questionnaire has shown high sensitivity and specificity for patients with heart rhythm disturbances, which further uses in different patients’ cohorts. The aim of our work was to evaluate acceptability, reliability, legitimacy and sensitivity of the Ukrainian-language modification of the Ferrans and Powers questionnaire for patients with AFl and AF before and after RFA. Materials and methods. The original Ferrans and Powers questionnaire, which consists of 15 questions, was translated and adapted from English into Ukrainian. The survey was conducted among patients before the RFA procedure, in the acute postoperative period (3–5 days), 3 months and 12 months after the procedure. According to the results, the sum of points was calculated and classes were allocated: class 1 (significant decrease in quality of life) – 15–44 points, class 2 (moderate decrease in quality of life) – 45–74 points and class 3 (slight decrease, or high quality of life) – 75–90 points. Acceptability, reliability, legitimacy and sensitivity of the survey scale were assessed. Results. The study included 118 patients with a mean age of 58.98 ± 9.6, 49 women (41.5 %). The scale of the Ukrainian-language modification of the Ferrans and Powers questionnaire had a high internal sequence (logic), the average correlation between the points of the scale was 0.51; Cronbach’s alpha coefficient is 0.9. All the recommended criteria for constructing such scales were agreed, 15 points were combined into a single scale, in which 32 % of discrepancies with the original points were observed. By acceptability, the highest and lowest extremes of quality of life were below the recommended maximum of 20 %. Reliability was confirmed by compliance with the recommended criteria of internal density and reproducibility in repeated measurements. A high intrinsic density was demonstrated, confirming the design-related validity of the questionnaire. The sensitivity of the proposed scale was reflected in the increase in the quality of life of patients after all types of RFA procedures. The study proved the high acceptability, reliability, validity and sensitivity of the quality of life questionnaire of patients with cardiac arrhythmia in patients with paroxysmal, persistent and persistent forms of AFl and/or AF, as well as their observation in the stages after RFA. Conclusions. The Ukrainian-language modification of the Ferrans and Powers questionnaire has high levels of acceptability, reliability, legitimacy and sensitivity for patients with AFl and AF, which is a useful practical tool for the treatment and control of these patients.